1980
DOI: 10.1172/jci109765
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fat-stimulated Gastric Inhibitory Polypeptide on Pancreatic Alpha and Beta Cell Function

Abstract: A B S T R A C T Gastric inhibitory polypeptide (GIP) is considered to be the principal mediator of the enteroinsular axis. A glucose-insulin clamp technique was used to study the effects of differing blood glucose levels on the insulinotropic and glucagonotropic actions of fat-stimulated GIP in seven healthy subjects, as well as the effect of physiologic hyperinsulinemia on GIP secretion. Blood glucose levels were clamped for 4 h at 43+2 mg/dl (hypoglycemic clamp), 88+1 mg/dl (euglycemic clamp), and 141+2 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…The significant improvement in the glycaemic level at test 2 after 1 week with near normalization of blood glucose concentrations did not induce any change in the mean concentrations of IR-GIP before, during or after the meal and the response was not different from that of the normal subjects. The reason for the discrepancy between this study and the above mentioned (Creutzfeldt & Ebert 1977;Verdonk et al 1980) may be the heterogeneity of IR-GIP Sarson et al 1980). In the present study more than 90% of the measured immunoreactivity is the 5000-dalton GIP (Krarup et al 1983) while other antisera also detect considerable amounts of the 8000-dalton GIP and a void volume component Finkeetal.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The significant improvement in the glycaemic level at test 2 after 1 week with near normalization of blood glucose concentrations did not induce any change in the mean concentrations of IR-GIP before, during or after the meal and the response was not different from that of the normal subjects. The reason for the discrepancy between this study and the above mentioned (Creutzfeldt & Ebert 1977;Verdonk et al 1980) may be the heterogeneity of IR-GIP Sarson et al 1980). In the present study more than 90% of the measured immunoreactivity is the 5000-dalton GIP (Krarup et al 1983) while other antisera also detect considerable amounts of the 8000-dalton GIP and a void volume component Finkeetal.…”
Section: Discussioncontrasting
confidence: 84%
“…In normal subjects the IR-GIP response to fat was diminished during a hyperglycaemic clamp when compared to that obtained during euglycaemia (Verdonk et al 1980). In untreated juvenile dia¬ betic fasting IR-GIP concentrations were markedly elevated while the IR-GIP response to a meal was insignificant (Creutzfeldt & Ebert 1977).…”
Section: Discussionmentioning
confidence: 87%
“…Interventions that change the plasma GIP concentration could, therefore, influence the insulin response to glucose. The available information on the effects of sulfonylureas on GIP secretion is controversial (28,29), and the physiologic regulation of GIP remains unclear (30,31). In our study the basal GIP concentration in the normal subjects was either unchanged (GZ) or decreased slightly (GB) after sulfonylurea administration.…”
Section: Healthy Nondiabetic Subjectsmentioning
confidence: 61%
“…For example, changes in the seum levels of gastric inhibitory polypeptide (GIP) have been shown to occur following introduction of intraduodenal amino acids and fatty acids [18]. In turn, GIP has been shown to en hance insulin secretion [19] and also pan creatic lipase production [20]. AynsleyGreen et al [21] have shown that both GIP and insulin significantly increase from basal levels, in preterm and full-term infants at birth to values in excess of mean adult fast ing values by 1-2 weeks of age.…”
Section: Discussionmentioning
confidence: 99%